Prussian blue-conjugated ZnO nanoparticles for near-infrared light-responsive photocatalysis - Fatima, Hira; Azhar, M.R.; Khiadani, M.; Zhong, Yijun; Wang, Wei; Su, Chao; Shao, Zongping (ELSEVIER SCI LTD, 2022)
Zinc oxide (ZnO)-based photocatalysis has great potential in wastewater treatment, but its photocatalytic performance suffers from the limitation of low-wavelength photon absorption. Herein, a near-infrared-responsive photocatalyst is developed to tackle this challenge, which is composed of Prussian blue (PB) dye conjugated iron oxide-zinc oxide hybrid nanoparticles (Fe3O4@PB@ZnO) with spherical morphology (∼14 nm). Fe3O4@PB@ZnO shows a higher-wavelength absorbance region centered at 781 nm as compared with PB-free Fe3O4-ZnO composite (Fe3O4@ZnO, 494 nm) and pristine ZnO (361 nm). The inclusion of a charge transfer band (FeII-CN-FeIII) after the conjugation of PB is responsible for such a profound absorbance shift. A comparative study of three samples as potential photocatalysts is performed in terms of the methylene blue degradation, which is found to be in an order of Fe3O4@PB@ZnO ˃ Fe3O4@ZnO ˃ ZnO. The enhanced photocatalysis rate of Fe3O4@PB@ZnO is credited to the lower bandgap of 1.2 eV from the presence of PB with low bandgap, retarded the recombination rate of electron-hole pair to produce enough reactive oxygen species from the rich surface vacancies and hole scavenging properties of PB. A plausible degradation mechanism of photocatalysis is proposed, revealing the singlet oxygen as the central point of enhanced performance.